Functional contribution of DCLKs in sea urchin development. Issue 8 (4th March 2021) - Xu, Derek; Wavreil, Florence D.M.; Waldron, Ashley; Yajima, Mamiko
Abstract: Background: Doublecortin‐like kinase1 and 2 (DCLKs) are protein Ser/Thr kinases important for neuronal development. More recently, they are also reported to regulate plasticity such as cell proliferation and differentiation of stem cells and cancer cells, but the details of their functions in this biological context are still unclear. With an attempt to reveal the functions of DCLKs in plasticity regulation, we here used the sea urchin embryo that undergoes highly regulative development as an experimental model. Results: We found that both the transcripts and the proteins of DCLKs are uniformly present during early embryogenesis and with some enrichment in mesenchymal cells after gastrula stage. Knockdown of DCLKs induced general developmental delay and defects at day 2. Further, the damage on the embryo/larva induced ectopic expression of DCLKs in the ectoderm where the damage was most severe. Under a tumor‐prone or ‐suppressive condition, DCLKs expression was upregulated or downregulated, respectively, after damage. In both cases, the embryos showed severe developmental defects. Conclusions: Taken together, a transient upregulation of DCLKs appears to be involved in a damage response both during normal and abnormal development, and which could result in different phenotypes in a context dependent manner. Key Findings: DCLK1 and DLCK2 (DCLKs) are both essential for proper embryonic development in the sea urchin. Expression of DCLKs is upregulated upon damage. A fine balance of Rb1 and Vasa activities appears to be critical for tight regulation of DCLKs expression.